1989
DOI: 10.1267/ahc.22.375
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody to keratin K8.12 expression in ductal basal cells of obstructive lesions and in outer tumor cells of salivary pleomorphic adenomas.

Abstract: Monoclonal antibodyfor keratin K8.12 (keratin nos. 13 and 16) was evaluated in paraffin sections of 17 cases of obstructive sialadenitis and 97 pleomorphic adenomas.In normal salivary glands fixed with 10% formalin, K8.12 staining was strongly limited to ductal basal cells, and staining to PKK1 and KL1 was positive in duct cells. Monoclonal antibodies PKK1 and KL1 were compared in duct-like structures of obstructive lesions and pleomorphic adenomas.Duct-like structures in obstructive lesions showed strong stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Cuboidal-shaped basal cells form a virtually continuous layer in the case of excretory ducts and gradually assume a discontinuous layer as the striated ducts become intralobular (Palmer et al, 1985;Caselitz et al, 1986;Dardick et al, 1987Shinohara et al, 1989). In some striated ducts, cuboidal basal cells become admixed with triangular-shaped cells and classically configured myoepithelial cells.…”
Section: B Basal/myoepithelial Cellsmentioning
confidence: 99%
“…Cuboidal-shaped basal cells form a virtually continuous layer in the case of excretory ducts and gradually assume a discontinuous layer as the striated ducts become intralobular (Palmer et al, 1985;Caselitz et al, 1986;Dardick et al, 1987Shinohara et al, 1989). In some striated ducts, cuboidal basal cells become admixed with triangular-shaped cells and classically configured myoepithelial cells.…”
Section: B Basal/myoepithelial Cellsmentioning
confidence: 99%
“…Ductal Basal Cell: Ductal Basal Cells in striated and excretory ducts of human salivary glands have been estimated in terms of keratin immunohistochemistry (38,50,81,84), and these basal cells also have important stem cells in neoplastic transformation of pleomorphic adenomas (72,95) tion with secretion of calcitonin. Other Factors: It has been reported that salivary glands in human and animals contain and secrete other growth factors and other growth factor-related substances identified by biological and biochemical studies, however cellular origin of these substances in salivary glands is still unknown.…”
Section: Calcitonin (Cat)mentioning
confidence: 99%
“…Their precise nature has aroused some controversy. Based on their stainability with antibodies to S100b protein and to various keratins (Palmer et al, 1985;Caselitz et al, 1986;Palmer, 1986;Born et al, 1987;Dardick et al, 1987Dardick et al, , 1988Geiger et al, 1987;Gustafsson et al, 1988;Shinohara et al, 1989) that stain endpiece myoepithelial cells (Dairkee et al, 1985), at least some of the basal cells have been labeled as myoepithelium or as "modified myoepithelium" by some authors (Mori et al, 1992a). Other authors have relied simply on the morphology of basal cells to justify their identification as myoepithelial cells (Chaudhry et al, 1987).…”
mentioning
confidence: 99%